Digital Marketing Strategies To Accelerate The Development Of Micro, Small, And Medium-Sized Enterprises (MSMES) In Indonesia - Rheince Sibarani (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia's economic development, contributing to employment, income generation, and entrepreneurship. However, many MSMEs face challenges in adapting to technological advancements, particularly in implementing digital marketing strategies. This study aims to analyze how digital marketing can accelerate the development of MSMEs in Indonesia through a literature review approach. The findings highlight that digital marketing provides MSMEs with opportunities to expand their market reach, increase brand visibility, and optimize costs. Social media platforms, e-commerce, and other digital tools enable MSMEs to connect with customers more effectively. Despite these benefits, barriers such as limited technological access, lack of digital literacy, and uneven internet infrastructure hinder the adoption of digital marketing. Collaborative efforts from the government, educational institutions, and the private sector are necessary to overcome these obstacles. Providing training, improving access to technology, and fostering innovation are crucial steps to support MSMEs in achieving sustainable growth.